Development of Digital Comic-based e-modules through Canva Application for Class X Students of Noemuti State Senior High School - NAIMNULE, LUSIA; Halek, Erlin Fatima; Fincensius Oetpah (ScienceEdu, 2025)
The study aims to describe the feasibility of electronic digital comic-based modules through Canva application for class X students of Noemuti State High School . This research was conducted at Noemuti State High School in August 2024. This research design refers to the research and Development (R & D) model of Thiagarajan, Semmel and Semmel consisting of four stages, namely: (1) defining (define), (2) planning (design) (3) development (development) in the form of device validation and e-module media as well as product trials on biology subject teachers and students and (4) dissemination (disseminate). The data obtained in this development research are qualitative data and quantitative data. Quantitative descriptive data analysis techniques were used to analyse data obtained from media expert validation sheets, material expert validation sheets, teacher assessment data and student assessment data obtained from questionnaires as respondents, which contained the feasibility of comic-based E-modules through the Canva application. The results of validation from material experts and media experts at stage I, namely material experts 76.25% and the results of validation from media experts are 78.94% and meet the feasible criteria. The results of the validation of material experts and media experts in stage II, 95.00% material experts and stage II media experts, 90.53%, meet the criteria of very valid or very feasible to be tested. The results of the Biology teacher assessment trial with a percentage of 97.00% meet the eligibility criteria very feasible. The results of the limited trial were 85.20%, while the small group trial was 88% with very feasible feasibility criteria. Thus it is stated that the digital comic-based e-module developed is suitable for use as teaching material for students.